Effects of calcination rate and temperature on microstructure and gaseous iodine capture capacity of 3DOM-SiO2 aerogels. (September 2022) - Chang, Sen; Wang, Kunjun; Wang, Longjiang; Song, Xuemei; Liu, Jingguo; Chen, Jianli; Yang, Kai; Zhang, Zhiquan; Li, Yongguo
Abstract: Three-dimensional ordered macropores silica (3DOM-SiO2 ) aerogels prepared by the sol-gel and colloidal crystal template technology have attracted wide attention in the field of gaseous radioiodine capture. 3DOM effectively reduces the diffusion resistance of gas, increases the specific surface area and improves the capture capacity of the aerogels. The optimization of the calcination process for removing colloidal crystal templates is very important for the construction of 3DOM. The effects of calcination rate and calcination temperature on the microstructure, specific surface area, surface official energy group, phase composition, and iodine adsorption capacity of 3DOM-SiO2 were systematically investigated. The results showed that the calcination rate and temperature affected the iodine capture capacity of 3DOM-SiO2 by affecting the formation of macropores, mesopores, and micropores and the content of adsorbed water in the pore structure. The optimization of the 3DOM preparation process provides a scientific basis for the capture and application of radioactive iodine. Graphical abstract: 3DOM-SiO2 exhibits the structural characteristics of three-dimensional ordered macropores-mesopores and abundant micropores after calcination at 300 °C for 1 h and 500 °C for 1 h with a heating rate of 1 °C /min, in which macropores-mesopores served as the diffusion pores and micropores worked as the adsorption pores, realizing the uniform adsorption of gaseous iodine. Image 1 Highlights: A three-dimensional ordered macroporous silica aerogel was successfully prepared. The detected iodine physisorption capacity of 3DOM-SiO2 reaches 15.2 ± 0.9 mg/g. The iodine capture mechanism of 3DOM-SiO2 aerogel was revealed.